Improving Students’ Creative Thinking In Learning Arabic Through HOTS Based Project Based Learning Model - Susanto Susanto; Ayu Desrani; Apri Wardana Ritonga; Yohan Rubiyantoro (Institut Agama Islam Negeri (IAIN) Metro, 2022)
This study aims to analyze students' creative thinking skills in learning Arabic through the application of a project-based learning model based on Hots. This study uses a quantitative approach with experimental methods of the type of quasi-experimental research with the research design used is Post-Test Only Control Group Design. The population in this study were students of class X MAN 1 Malang City, East Java, Indonesia. The data collection instrument used was a test using an independent sample t-test analysis test. Based on the independent sample t-test, the significance value of the variable analysis was 0.013 < 0.05 with an average value of 75.12 for the experimental class and 70.28 for the control class. Through the results obtained, there is a significant positive effect between experimental class students who use project-based learning models and control class students who only use conventional models. So to improve students' creative thinking skills, they can use project-based learning in Arabic learning.